Literasi Teknologi Informasi (Mazahib, 2014)
Globalisation bring world as a global village.  All informations from different culture can catch easily in real time.  So all people must have skill and knowledge when access information.  Information must be selected, just information that compatible with what they need they will use. When all people use all needed informations effectively, its called they literate generation.  Next, as subject of law, literate generation must look carefully legal and ethical issues as a part of intercultural awareness, intellectual learning and intercultural skills.